Pushing Boundaries: Reflections on the 2022 International FEMGEOG Conference - Colls, Rachel; Fluri, Jennifer; Boonabaana, Brenda; Coddington, Kate; Datta, Anindita; Faria, Caroline; Klosterkamp, Sarah; Meletis, Zoë; Trauger, Amy; Williams, Jill; Worth, Nancy (ACME, 2025)
The following paper discusses and reflects upon the practices of organizing and attending the 2022 hybrid International Feminist Geography Conference (FEMGEOG), held in a range of physical and virtual locations and settings and across time zones. Through a series of short reflections written by members of the organizing committee it considers the practices of conference planning and organization alongside people’s experiences of their involvement and participation at different stages of the endeavour. The title of the conference, Pushing Boundaries, represents how the ethos and organisation of the conference sought to push against pandemic related travel restrictions, academic hierarchies of knowledge production and the financial inequities of conference attendance. It aimed to foster new means of connection, community and ways of relating to each other, and our research, through its international, multi-hub format. The paper also discusses the tensions and difficulties of organising an event of this kind, with reference to workload, funding and the technological demands and competencies required to foster inclusivity and connection. These reflections work as a means to provide advice and support for feminist geographers in the development of similar, future events.